Answer:
[tex]B = (x+4,y-2)[/tex]
Step-by-step explanation:
Let the current position be A:
[tex]A = (x,y)[/tex]
Required
Determine the new position
First, you move 4 units to the right.
This is represented as [tex]x + a[/tex]
Where a is the number of units to the right
In this case:
[tex]a = 4[/tex]
So, we have: [tex]x + 4[/tex]
Then you move 2 units downwards
This is represented as [tex]y - b[/tex]
Where b is the number of units downwards.
In this case:
[tex]b = 2[/tex]
So, we have: [tex]y - 2[/tex]
So, the new position (B) is:
[tex]B = (x+4,y-2)[/tex]